1991
DOI: 10.1002/jcp.1041470118
|View full text |Cite
|
Sign up to set email alerts
|

Growth and differentiation of primary tracheal epithelial cells in culture: Regulation by extracellular calcium

Abstract: Growth and differentiation of primary monkey tracheal epithelial (MTE) cells maintained on collagen gel substrata were studied in a defined serum-free culture medium containing 0.03 to 3.0 mM extracellular calcium. Cell attachment efficiency (40-60%) was not altered by different calcium levels. Growth of primary MTE cells on collagen gel substrata, which was vitamin A dependent, was enhanced 50% in the medium supplemented with high calcium (greater than 0.3 mM). High calcium medium also increased cell-cell int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…We observed that the expression of mucous cell function is dependent on the concentration of calcium in the medium. These studies demonstrate that >0.3 mM calcium in culture medium is needed to achieve mucous cell differentiation [24].…”
Section: Effects Of Calcium Levelsmentioning
confidence: 73%
See 1 more Smart Citation
“…We observed that the expression of mucous cell function is dependent on the concentration of calcium in the medium. These studies demonstrate that >0.3 mM calcium in culture medium is needed to achieve mucous cell differentiation [24].…”
Section: Effects Of Calcium Levelsmentioning
confidence: 73%
“…Furthermore, the quantitative kinetics and the time-course studies suggest that the mucous cell population in the hamster culture is derived from the undifferentiated cell type. Evidence of in vitro mucous cell differentiation has now been extended to cultures derived from monkey [23,24], human [6], rabbit [25], and guinea pig [26] airway tissues. Recently, the development of mucinspecific monoclonal antibodies allow us to use both the enzyme-linked immunosorbent assay (ELISA) [16] and immunohistochemical methods [6] to quantify mucin production and mucous cell population, respectively, in culture.…”
Section: Evidence Of Mucociliary Cell Differentiation In Culturementioning
confidence: 99%
“…72 This allowed the development of ALI cultures originally with guinea pig tracheal epithelial cells. 118 ALI cultures were rapidly adopted for use with primate, 119 human, 120,121 rat, 122 bovine 123 and canine 124 tracheal epithelial cells.…”
Section: Submerged Versus Alimentioning
confidence: 99%
“…The role of vitamin A in regulation of epithelial differentiation has been established for: mucin genes [47]; cytokeratins [48], markers of squamous cell differentiation [39]; small proline-rich protein [49][50][51]; an antioxidant, thioredoxin [52]; the cytokine, interleukin (IL)-8 [53]; epithelial growth factor [54]; and heterogeneous nuclear protein AI [55]. Extracellular calcium also plays a role in epithelial differentiation in vitro [56].…”
Section: Mucociliary Epithelium In Rhesus Monkeysmentioning
confidence: 99%